Financial Intelligence Units Working with Law Enforcement Authorities and Prosecutors - Stroligo, Klaudijo (World Bank, Washington, DC, 2019)
This publication "Financial Intelligence Units Working With Law Enforcement" supports the implementation of the international anti-money laundering/countering financing of terrorism (AML/CFT) standards promulgated by the Financial Action Task Force (FATF) and other international organizations, and to propose good practices in cooperation among financial intelligence units (FIUs), law enforcement agencies and prosecutors (LEAs). Another objective is developing practical solutions to assist jurisdictions in better demonstrating how financial intelligence is effectively managed among the competent authorities responsible for combating money laundering, associated predicate offences, and terrorist financing. The publication is based on a joint study by StAR, the Egmont Group, and United Nations Office on Drugs and Crime - Global Programme against Money Laundering (UNODC GPML). In many jurisdictions, the level of cooperation between FIUs and LEAs could be significantly improved. StAR's new publication examines how the FIUs and LEAs cooperate with one another and identifies the impediments to their closer cooperation. Based on findings among a survey of FIUs and LEAs, and extensive consultations, the publication sets forth practical solutions to improve cooperation and the effective management of financial intelligence. In addition, the publication presents recommendations for policy makers to improve their policies related to the cooperation among FIUs and LEAs.